KARAKTERISASI DAN UJI POTENSI JAMUR ENDOFIT PADA DAUN BAWANG MERAH (Allium ascalonicum L.) SEBAGAI PENGENDALI PATOGEN Fusarium sp. dan Alternaria sp. - Mita Erliza; Syafrina Sari Lubis (KENANGA : Journal of Biological Sciences and Applied Biology, 2023)
Shallot (Allium ascalonicum L.) is a horticultural commodity that has high economic value and is needed every day by the community. Attack by pets and pathogens on shallot cultivation cause a decrease in crop productivity. The pathogen that often attacks shallot plants is Fusariumsp. and Alternaria sp. This study aims to obtain endophytic fungi from shallot leaves that can control Fusarium sp. and Alternaria sp. The endophytic fungus isolation method uses healthy shallot leek samples while the pathogen isolation uses unhealthy leaves. The antagonism potency test was conducted using the dual culture method with an incubation time of 7 days at 25-30oC. Based on the results of the study, there were 4 isolates of endophytic fungi on shallot leaves, namely EA1 isolates (Aspergillus niger), EA2 isolates, EA3 isolates (Clasdoporium sp.) and EA4 isolates (Phyllosticta sp.). The results of the antagonist test showed that the endophytic fungus EA1 was able to inhibit the fungus Fusarium sp. and Alternaria sp. maximally (strong) with an average value of Fusarium sp. of 62.72% while Alternaria sp. 67.83 %. The endophytic fungus EA2 was also able to inhibit both of these pathogens but it was moderately categorized with an average value of Fusarium sp. 52.11 % and Alternaria sp. 53.28%. The mechanisms of inhibition are competition and hyperparasitism.